Peer Tutoring Technique: Helping Students Reducing Fear In Improving Speaking Ability - admin admin; Paulina paulina (Universitas Muhammadiyah Gresik, 2017)
The study was aimed to solve the problem in the speaking class dealing with the students fear and the bad quality of speaking ability using peer tutoring technique. The design of the study is Classroom Action Research (CAR) which involves 26 students assigned in intermediate speaking class in English Department of University of Muhammadiyah Gresik. The preliminary study conducted showed that students had a fear to speak in front of the class which resulted in their speaking skill quality. The study offered one cycle consisted of planning, observing, implementing, and reflecting. the cycle took two meetings. The students were divided into two groups of high speaking ability and low speaking ability. The two groups were divided again into small units called pair. In one pair, the high speaking ability students taught the low speaking ability students before they had individual presentation in front of the class. In the end of the cycle, the peer tutoring process showed that students achieved thyeir average score above the minimum passing level of 60, which was the criteria of success.